2016
DOI: 10.1016/j.celrep.2016.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Induce Endocrine Differentiation in Pancreatic Ductal Cells via STAT3-Dependent NGN3 Activation

Abstract: SUMMARY A major goal of diabetes research is to develop strategies that replenish pancreatic insulin-producing beta cells. One emerging strategy is to harness pancreatic plasticity—the ability of pancreatic cells to undergo cellular interconversions—a phenomenon implicated in physiological stress and pancreatic injury. Here we investigated the effects of inflammatory cytokine stress on the differentiation potential of ductal cells in a human cell line, in mouse ductal cells by pancreatic intraductal injection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 53 publications
1
57
1
1
Order By: Relevance
“…However, recent studies have demonstrated a critical role for Stat3 in pancreatic cell homeostasis (46,47). Here, early activation of Stat3 overcomes FoxO1 suppression, leading to β-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated a critical role for Stat3 in pancreatic cell homeostasis (46,47). Here, early activation of Stat3 overcomes FoxO1 suppression, leading to β-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…At the mature stage, infiltrated macrophage cells were observed frequently in the islet of Tg mice [53]. Chemokine/cytokine-induced epithelial-mesenchymal transition (EMT) in the process of β -cell neogenesis from ductal cells was proposed recently [70]. A similar induction mechanism to that of EMT is likely to be involved, at least partially, in generating new β -cells from duct-like structures, in which the secreted cytokines and chemokines play relevant roles in Tg mice because of SASP-like characters of β -cells [52] and by recruited macrophage cells to the islet [53].…”
Section: Unusual Ductal Structures In the Pancreasmentioning
confidence: 99%
“…Islet regeneration depends on protein kinase A/signal transducer and activator of transcription 3 (PKA/STAT3) signaling‐mediated NGN3 activation . WB analysis on the retrieved pancreases, at short‐ and long‐term post‐TX, detected STAT3 protein, although in our experimental system we have not confirmed the presence of pSTAT3(TYR705) (data not shown).…”
Section: Resultsmentioning
confidence: 61%